2013
DOI: 10.1016/j.jaut.2013.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Using EAE to better understand principles of immune function and autoimmune pathology

Abstract: Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system (CNS) in which myelin becomes the target of attack by autoreactive T cells. The immune components of the disease are recapitulated in mice using the experimental autoimmune encephalomyelitis (EAE) model. EAE is classically induced by the immunization of mice with encephalitogenic antigens derived from CNS proteins such as proteolipid protein (PLP), myelin basic protein (MBP) and myelin oligodendrocyte glycoprotein (MOG). Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
156
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(164 citation statements)
references
References 117 publications
2
156
0
3
Order By: Relevance
“…It is induced by the administration of myelin antigens. The most frequent EAE model used is C57BL/6 mice injected with the MOG [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] peptide [16,17], and it has been the major tool to understand the mechanism involved in MS pathogenesis, as well as to test therapies for the human disease. To determine the effect of a therapy in EAE, three different approaches can be used: preventive (before immunization), preclinical (postimmunization) and therapeutic (after the onset of the disease) [17].…”
mentioning
confidence: 99%
“…It is induced by the administration of myelin antigens. The most frequent EAE model used is C57BL/6 mice injected with the MOG [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] peptide [16,17], and it has been the major tool to understand the mechanism involved in MS pathogenesis, as well as to test therapies for the human disease. To determine the effect of a therapy in EAE, three different approaches can be used: preventive (before immunization), preclinical (postimmunization) and therapeutic (after the onset of the disease) [17].…”
mentioning
confidence: 99%
“…With a prevalence of 2.5 million patients worldwide, MS is the most frequent autoimmune disorder of the CNS. Studies in humans and mice demonstrated a prominent role of CD4 T cells in the pathogenesis of autoimmune demyelinating diseases, in particular of T-bet1/IFNγ-positive Th1 cells and RORγt/IL-17-positive Th17 cells (3)(4)(5)(6). Current therapeutic concepts for the treatment of MS include i.v.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental autoimmune encephalomyelitis (EAE) is an animal model for the early inflammatory phase of human multiple sclerosis, but it is also useful to deepen the understanding of Th cell functions in a disease situation in vivo (19,20). To induce EAE, an immune reaction is initiated against a part of the myelin that surrounds nerve cells.…”
mentioning
confidence: 99%